Measuring the frequency and distribution of meiotic crossovers in homozygous barley inbred lines - Schreiber, Miriam; Chen, Yun-Yu; Ramsay, Luke; Waugh, Robbie (Frontiers in Plant Science, 2022)
We report a novel approach for establishing the number and position of CO events in individual homozygous inbred plants by combining low level EMS mutagenesis, speed breeding, whole genome shotgun sequencing and sliding window analysis of the induced molecular variant data. We demonstrate the approach by exploring CO frequency and distribution in self-fertilised progeny of the inbred barley cultivar Bowman and compare these observations to similar data obtained from a nearly isogenic line (NIL) containing a mutation in the DNA mismatch repair gene HvMLH3. We have previously shown that Hvmlh3 decreases both plant fertility and recombination by ~50% (Colas et al., 2016). We compare our results to those from previously published traditional genetic analysis of F3 families derived from multiple F2 lines containing WT or mutant alleles of HvMLH3, revealing a high level of correspondence between analyses. We discuss possible applications of the approach in streamlining the assessment of recombination in plant meiosis research.